1991
DOI: 10.1084/jem.174.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Selective expression of a VHIV subfamily of immunoglobulin genes in human CD5+ B lymphocytes from cord blood.

Abstract: During the past few years, heterogeneity within B lymphocyte populations has become increasingly apparent. Several studies have demonstrated functional, physiological, and developmental heterogeneity. Studies in the mouse suggested that two separate lineages of B cells may exist (1) . One lineage, is defined by cell surface expression of the Ly-1 antigen, characteristic of T lymphocytes, and the secretion of polyspecific antibodies reactive with a variety of self antigens. The second lineage lacks the Ly-1 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…It is therefore tempting to speculate that the underrepresentation of VH4-34 cells in germinal centers and germinal center-derived B cells and plasma cells could be the result of their positive selection into a separate anatomic and functional compartment, perhaps a human "B1-like" compartment. Such interpretation is consistent with the observation that VH4-34 antibodies are frequently made by human cord blood CD5 + B cells but are absent from CD5 -cells (64). Yet, this dichotomy is not preserved in the adult and singlecell PCR analysis of adult IgM B cells has demonstrated similar expression of VH4-34 in CD5 + and CD5 -cells (65).…”
supporting
confidence: 74%
“…It is therefore tempting to speculate that the underrepresentation of VH4-34 cells in germinal centers and germinal center-derived B cells and plasma cells could be the result of their positive selection into a separate anatomic and functional compartment, perhaps a human "B1-like" compartment. Such interpretation is consistent with the observation that VH4-34 antibodies are frequently made by human cord blood CD5 + B cells but are absent from CD5 -cells (64). Yet, this dichotomy is not preserved in the adult and singlecell PCR analysis of adult IgM B cells has demonstrated similar expression of VH4-34 in CD5 + and CD5 -cells (65).…”
supporting
confidence: 74%
“…As in human cord blood, CD5 + B cells are present in early in life in normal mice 13, 36, 37 . One day after birth in ON25 mice (heterozygous knock-in), nearly all newly generated immature B cells in the liver expressed the V H Q52id + μ heavy chain, most with a κ light chain (Figure 2e top).…”
Section: Resultsmentioning
confidence: 96%
“…However, the differential expression patterns of Lin28b that distinguishes fetal and adult hematopoietic cells in mice has also been found in humans 17 , and CD5 + B cell generation, including at the immature stage, is the predominant outcome of development in the human fetus and in cord blood 36, 37, 59 . Since the level of TdT is lower in human fetal development than adult, but is upregulated much earlier than in mice 60 , N-addition in human V H 1-69/D3-16/J3 with a longer CDR3 does not exclude fetal/neonatal generation.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide sequence analysis of the VH and VL monoreactive high affinity of an IgG anti-DNA antibody secreted by a monoclonal (T14) from an EBV-transformed B cell line from a patient with active SLE showed that V,,T14 is 94.8% homologous with the germline VH4.21 gene segment and VLT14 is 98.6% ho mologous to the germline kv325 gene segment of the VkI I lb subfamily [34], Comparison of the VM 4T14 and VkIIIb.T14 and their respective germlinc genes showed a nonrandom distribution of silent and replacement muta tions in the combined CDR region, supporting the process of antigen-driven B cell activation and selection. Interest ingly, kv325 is also known to be overrepresented in ne oplasms that commonly bear the CD5 antigen and in Epstein-Barr virus (EBV)-transformcd cell lines derived from CD5+ cord blood cells [41,42]; the gene segment en coding T14 shows a striking overlap with those frequently expressed in natural anti-DNA antibodies [34].…”
Section: S O M a Tic M Utationsmentioning
confidence: 99%